2001
DOI: 10.4049/jimmunol.166.4.2522
|View full text |Cite
|
Sign up to set email alerts
|

Selective Gene Expression and Activation-Dependent Regulation of Vasoactive Intestinal Peptide Receptor Type 1 and Type 2 in Human T Cells

Abstract: Vasoactive intestinal peptide (VIP) has potent antiproliferative and anti-inflammatory functions in the immune system. Two structurally distinct G-protein-associated receptors, VIP receptor type 1 (VPAC1) and VIP receptor type 2 (VPAC2), mediate the biological effects of VIP. The regulation of VIP receptor gene expression and the distribution of these receptors in different compartments of the human immune systems are unknown. This study reports, for the first time, a quantitative analysis of VPAC1 and VPAC2 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
112
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(122 citation statements)
references
References 45 publications
(43 reference statements)
10
112
0
Order By: Relevance
“…Previous data reported by Takeba et al (32) had already suggested that VPAC 2 was the only receptor expressed and functional in FLS, based on data limited to RA FLS. Previous data in rodent and human myeloid and lymphoid cells have also shown a different distribution and regulation of VPAC 1 and VPAC 2 (33,34). Monocytes and T cells also constitutively express VPAC 1 , whereas VPAC 2 is inducible by specific cell activation (35)(36)(37).…”
Section: Discussionmentioning
confidence: 90%
“…Previous data reported by Takeba et al (32) had already suggested that VPAC 2 was the only receptor expressed and functional in FLS, based on data limited to RA FLS. Previous data in rodent and human myeloid and lymphoid cells have also shown a different distribution and regulation of VPAC 1 and VPAC 2 (33,34). Monocytes and T cells also constitutively express VPAC 1 , whereas VPAC 2 is inducible by specific cell activation (35)(36)(37).…”
Section: Discussionmentioning
confidence: 90%
“…64 Another molecule in the focus of the review by Perez Leiros is vasoactive intestinal peptide (VIP), whose anti-inflammatory and tolerogenic effects were already known. 65 It is now known that VIP levels rise at the fetal-maternal interface at early gestation peaking at placentation begin. 66 Its role in embryogenesis was revealed after observing that its blockade during midgestation ends in induced growth retardation and microcephaly.…”
Section: Modulators Of the Immune Responses During Pregnancymentioning
confidence: 99%
“…In naïve, mouse and human CD4 and CD8 T lympho- cytes, the constitutively expressed VPAC1 receptor is 300-500-fold higher than VPAC2 [12,[45][46][47] (unpublished data) at the mRNA and protein levels that appears to be inversely related to the expression level of IL-2. Our laboratory has recently identified the VIP/VPAC1 transcriptome in naïve and activated mouse splenic CD4 T cells.…”
Section: Vip Receptor Expression Profile and Its Transcriptome In T Lmentioning
confidence: 99%
“…In rodent leukemia T cell lines of various etiologies, all cell lines studied exclusively expressed VPAC2, some of which were validated to be functional [57,[82][83][84] . A VPAC2 predominant expression profile in cancer is unusual as VPAC2 expressing tumors are rare [74] , and that the expression profile of healthy peripheral lymphocytes express extremely high VPAC1 at both the mRNA and protein levels [45] . Malignant T cells from ALL patients occur due to a blockade in thymocyte development (thymic in origin), or from a blockade in HSC within the bone marrow (prethymic) [85] .…”
Section: Vip Signaling Axis and T Cell Leukemiamentioning
confidence: 99%